2012
DOI: 10.1002/jcb.24132
|View full text |Cite
|
Sign up to set email alerts
|

Novel Polypyridyl chelators deplete cellular zinc and destabilize the X‐linked inhibitor of apoptosis protein (XIAP) prior to induction of apoptosis in human prostate and breast cancer cells

Abstract: X-linked inhibitor of apoptosis protein, XIAP, inhibits the initiation and execution phases of the apoptotic pathway. XIAP is the most potent member of the inhibitor of apoptosis protein (IAP) family of the endogenous caspase inhibitors. Therefore, targeting XIAP may be a promising strategy for the treatment of apoptosis-resistant malignancies. In this study we systematically studied the relationships of chemical structures of several novel ligands to their zinc-binding ability, molecular target XIAP, and tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…94, 95 Indeed, TPEN-mediated XIAP depletion coincides with increased activation of the apoptosis-mediating caspase 3 and caspase 9, as well as increased sensitization of apoptosis-resistant tumour cells to subsequent treatment with TNF-related apoptosis-inducing ligand (TRAIL). 93 These findings were also supported by Zuo et al , 96 who demonstrated that novel polypyridyl chelators deplete cellular zinc and destabilize XIAP in human prostate and breast cancer cells. In light of the fact that prostate cancer cells are unable to counteract zinc chelation, a new potential therapeutic avenue opens for exploration.…”
Section: Therapeutic Applications Of Zincmentioning
confidence: 54%
“…94, 95 Indeed, TPEN-mediated XIAP depletion coincides with increased activation of the apoptosis-mediating caspase 3 and caspase 9, as well as increased sensitization of apoptosis-resistant tumour cells to subsequent treatment with TNF-related apoptosis-inducing ligand (TRAIL). 93 These findings were also supported by Zuo et al , 96 who demonstrated that novel polypyridyl chelators deplete cellular zinc and destabilize XIAP in human prostate and breast cancer cells. In light of the fact that prostate cancer cells are unable to counteract zinc chelation, a new potential therapeutic avenue opens for exploration.…”
Section: Therapeutic Applications Of Zincmentioning
confidence: 54%
“…All specimens were formalin fixed, sectioned, stained with haematoxylin and eosin and examined through microscopy. Pathological staging was performed by Dr Chang according to the international staging system for lung cancer 67 .…”
Section: Methodsmentioning
confidence: 99%
“…Also, polypyridyls are acyclic chelators that have proven their ability to treat apoptosis‐resistant human cancer in vitro due to their strong zinc chelating properties (Zuo et al . ). Examples of polypyridyls (Fig.…”
Section: Introductionmentioning
confidence: 97%
“…) include di‐(2‐picolyl) amine (DPA) and N,N,N′,N ‐tetrakis (2‐pyridymethyl) ethylenediamine (TPEN) which has a higher affinity for zinc metals than DPA (Zuo et al . ). The zinc chelating properties of TPEN have been studied both in vitro and in vivo , but there is very little information in the literature on the MBL inhibition properties of these acyclic chelators (Adler et al .…”
Section: Introductionmentioning
confidence: 97%